Interest of National Health Insurance Owners in Informal Sector in the Use of First Level Health Facilities in Jambi City - Dwi Noerjoedianto; Andi Subandi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The highest coverage of JKN participation in Jambi Province is the Jambi city. However, the size of JKN participation in Jambi city is not proportional to its use. This study aims to determine the interest of the owners National Health Insurance in informal sector in the use of first-level health facilities in the Jambi city. This research was conducted with quantitative methods using aapproach cross sectional. The population in this study are all informal workers whose population is unknown. The sample in this study are 105 respondents, the sampling technique was used purposive sampling. Bivariate results using the chi-square test, the relationship between the independent variable and the dependent variable, age (p=0,130), gender (p=0,401), education (p=0,134), income (p=0,183), knowledge (p=0,057), health facilities (p=0,174) , needs (p=0,000) with interest in using health insurance. The owners of the informal sector JKN in Jambi city was interested using first-level health facilities and there is a relationship between needs and interests of JKN owners in informal sector in the use of the first-level health facilities Jambi city